3(p+6)=-(2p+2)

Simple and best practice solution for 3(p+6)=-(2p+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(p+6)=-(2p+2) equation:



3(p+6)=-(2p+2)
We move all terms to the left:
3(p+6)-(-(2p+2))=0
We multiply parentheses
3p-(-(2p+2))+18=0
We calculate terms in parentheses: -(-(2p+2)), so:
-(2p+2)
We get rid of parentheses
-2p-2
Back to the equation:
-(-2p-2)
We get rid of parentheses
3p+2p+2+18=0
We add all the numbers together, and all the variables
5p+20=0
We move all terms containing p to the left, all other terms to the right
5p=-20
p=-20/5
p=-4

See similar equations:

| 8^(2x-2)=64 | | -2x(5x-7)+(3x+2)=4x-2(3+x) | | 16x-40+x=4x+10+8 | | 9/s=5/ | | X2=19x-88 | | 2(x+17)-4=16 | | 7(x+4)−6(x+3)=x+5 | | (2t5+4)+3/5×20=0 | | 2x+5=1x-10 | | 2x+20=9x+27 | | 2x+5x=1x-10 | | 2*6x+2-8x-6=0 | | 37x+13=6(6x+2) | | 3x+x=116 | | (3x)5.85+4.7x=600.75 | | 5(2q-1)=30q | | 5(w-8)=9w-26 | | 17x+16=-12 | | -8t-3t+2-5t-6t-0.3(t-4)+t=0.5(3-t) | | 7(6v-3)=14 | | 12=4x^2−6x+2 | | 12=4x2−6x+2 | | 11x=-50 | | 12+2y=48 | | (4x-3)/7=3 | | 11x=50 | | 6x+0=48 | | -10(w-1)+5(2w-4)=-w+(3w+24) | | |u-2|=-1/9 | | -u/7=-45 | | (3x+1)^1/2=2 | | 2(p+10)=4-4(5p-4)+21p |

Equations solver categories